Conflicting sociabilities and residential alienation. The Rental housing discomforts in settlements popular consolidated from Lima Sur - García Cristóbal, Anderson A. (2020)
In this article we discuss the submarket of rental housing, based on the discomforts of this tenure regime in consolidated popular settlements in southern Lima; from the concepts of sociability and subjectivity. Through the first concept, we describe how this housing system is generating highly conflictive relationships. The second concept addresses how that tenancy experience is lived as residential alienation. We finish showing how the residential experience of the tenants presents us the worst side of densification. At last, we propose some recommendations for public policy.